Cartes et propagande a la Conference de la Paix de Paris en 1919-1920 - David, Anne (Univerzita Pardubice, 1998)
The peace conference in Paris in 1919-1920 was the first international conference to prove the importance of maps. The participating countries tried to support their demands by all means including cartography. The specialist committees (especially university teachers, historians and geographists) tempted to formulate their countries' demands by using maps. The committees had been preparing the conference negotiations since 1917 already trying to support the individual state representatives in the discussions. The geographic description did not always reflect the reality, no matter how hard the map authors tried. The statistics were not very reliable and sometimes they were even used for propaganda. This was the origin of certain differences between scientific feature of the descriptions and the reality. In other words - between the borders they struggled for and the feasible borders.
Keywords: Pařížská mírová konference; 1. světová válka; mapy